2013
DOI: 10.5812/jhs.9885
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Knowledge and Practice Regarding Childhood Diarrhea and Diet in Zahedan, Iran

Abstract: Background: Diarrhea infection has been established as one of the major etiologies and risk factors of malnutrition in children. Objectives:The aim of this study was to assess the maternal knowledge, attitude and practices when treating diarrhea in their children less than 5 years old in the Zahedan, south-east province of Iran. Materials and Methods:This cross-sectional study was conducted in urban health centers in Zahedan. Three hundred mothers who had less than five years old children and had been referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 19 publications
8
17
0
1
Order By: Relevance
“…Our results also showed that 39.2% of the mothers knew about signs of child diarrhoea. This result is comparable to surveys conducted previously in the North of Iraq (Sulaimania) [32], Iran (Zahedan) [33], Odisha [34], Tanzania (Mkuranga) [35], which reported the low level of mothers' knowledge about signs of diarrhoea. The WHO/UNICEF indicated that the mothers/caregivers perception of the signs of child diarrhoeal disease is a major determinant of the choice of care sought to reduce the risk of illness [36].…”
Section: Discussionsupporting
confidence: 86%
“…Our results also showed that 39.2% of the mothers knew about signs of child diarrhoea. This result is comparable to surveys conducted previously in the North of Iraq (Sulaimania) [32], Iran (Zahedan) [33], Odisha [34], Tanzania (Mkuranga) [35], which reported the low level of mothers' knowledge about signs of diarrhoea. The WHO/UNICEF indicated that the mothers/caregivers perception of the signs of child diarrhoeal disease is a major determinant of the choice of care sought to reduce the risk of illness [36].…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, 68.29% mother increased breastfeeding during diarrhoea in our study. The source of information about different aspects of diarrhoea was physicians in 51% and health care staffs in 44.6% of participants in their study [14]. Results about source of knowledge are similar to ourstudy.…”
Section: Original Research Articlesupporting
confidence: 84%
“…disease as the reason for the runs. Cabatbat, et al in their examination led in Philippines reports 77%, 34% and 23% moms recognizing dangerous drinking water, inability to wash hands in the wake of pooping, and subsequent to taking care of loose motion separately as regular purposes behind diarrhoeal diseases 14,15,16 . Knowledge with respect to the eating regimen to be pursued amid a scene of loose bowels is likewise restricted among the moms.…”
Section: Discussionmentioning
confidence: 99%
“…This means 328 loose bowels passing consistently per day and 13 consistently per hour. To be seen from [11][12][13][14][15][16][17][18][19][20][21][22][23] July, the Health Ministry propelled the across the nation 'Increased Diarrhoea Control Fortnight' (IDCF) 2 under which diff erent exercises have been arranged including visits by Accredited Social Health Activist (ASHA) specialists to every single such family unit which have kids younger than fi ve. "ASHA specialists will visit all family units with kids beneath fi ve years old for preparation and diff erent aspect of ORS the ORS.…”
Section: Introductionmentioning
confidence: 99%